A community of care: Student conduct during the Covid‐19 pandemic. Issue 176 (28th February 2022) - Hunter, Kendra L.; LaRoche, Catherine H.; Morgan, Chad W.
Abstract: During the COVID‐19 pandemic, universities adjusted policy and protocols to manage the environment and mitigate the risk of virus transmission among the campus community. In the early semesters of the pandemic, these changes restricted student behavior that would have otherwise been encouraged, such as attending gatherings, and often resulted in conduct violations that had penalties, including removal from campus. This article will explore how one university implemented a Community of Care ethos to promote the health, safety, and wellbeing of the campus community and will identify the challenges and lessons learned during the COVID‐19 pandemic.